Impact of the Health Transformation Plan on the Number of Surgical Operations and Their Cancelation - MahmoodReza Miri Bonjar MD; Mohammad Khammarnia PhD; Mahdie Bakhshi MSc; Alireza Ansari-Moghaddam PhD; Hassan Okati-Aliabad PhD; Mehdi Mohammadi PhD (SAGE Publishing, 2019)
Operation cancelations are a serious problem with undesirable consequences. The Health Transformation Plan was launched in the health system of Iran on May 5, 2014, to enhance the efficiency and quality of services in public hospitals. Comprehensive coverage of patients' basic treatment needs and reduction of patients' out-of-pocket expenditures through insurance for all are other objectives of Health Transformation Plan as well. Then, the present study aimed to determine the impact of the Health Transformation Plan on the number of surgical operations and the cancelation of elective surgeries within public hospitals of Iran. This retrospective comparative study was conducted in 2017 within 2 tertiary public hospitals in the South-East of Iran. Using systematic random sampling method and census, 8138 scheduled surgical files and all canceled operations files were reviewed from April 2012 to March 2017, respectively. A standard checklist was used for data collection. The data were analyzed using χ 2 test and a logistic regression model in SPSS, version 21. The study population was 8138 patients with mean age of 33 ± 19 years. Female patients comprised about 51% of the study population (n = 4115), and nearly two-third of them were married (n = 5192 [63.79%]). Coverage by Iranian health insurance was reported in more than half of patients (n = 4415 [54.79%]). The common reason for surgeries was injury and poisoning (n = 2814 [34.52%]) followed by delivery (n = 1747 [21.46%]). The number of operations increased from 26 677 before Health Transformation Plan (cancelation rate = 1.5%) to 33 190 after Health Transformation Plan (cancelation rate = 2.0%). The cancelation rate had a significant relationship with age (odds ratio = 1.009; confidence interval: 1.00-1.01), health insurance status (odds ratio = 2.12; confidence interval: 1.33-3.38), outpatient service referrals (odds ratio = 0.5; confidence interval: 0.43-0.62), inpatient service referrals (odds ratio = 1.5; confidence interval: 1.36-1.77), and surgical types ( P < .05). In general, the Health Transformation Plan was markedly associated with a rise in the number of surgeries and cancelation rate in the public hospitals. The information obtained in the present study concerning the causes of operation cancelations can be used to decrease the number of future cancelations.